Comparing nanofiltration membranes effectiveness for inorganic and organic compounds removal from a wastewater-reclamation plant's micro-filtered water. (2021) - Jamil, Shahzad; Loganathan, Paripurnanda; Kandasamy, Jaya; Ratnaweera, Harsha; Vigneswaran, Saravanamuthu
Abstract: The study compared five NF membranes with varied water contact angles and molecular weight cut-off (MWCO) values for their effectiveness to remove dissolved organic carbon (DOC) and inorganic ions from micro-filtered water obtained from a wastewater-reclamation plant. The NF 90 membrane with the highest contact angle (79 0, least hydrophilic) and one with the lowest MWCO value ((90–200 Da) was the most efficient in removing DOC (88% rejection compared to 37–84% for the others) and inorganics (75% electrical conductivity rejection compared to 9–27% for the others). Of the 10 organic micropollutants in the feed water, >90% of 7 were removed.